Business accomplishments, gender and entrepreneurial self-image - Verheul, Ingrid; Uhlaner, Lorraine; Thurik, Roy (Journal of Business Venturing, 2005)
Drawing on Bem's psychological theory of self-perception, this paper presents and tests a model that examines the impact of business accomplishments and gender on entrepreneurial self-image and explores the definition of entrepreneurship according to Vesper's entrepreneurial typology. Regression techniques are used to identify those business accomplishments that university alumni associate with self-perceptions of entrepreneurship. Experience as a small business person (founding, running, and/or owning a small business) most clearly predicts entrepreneurial self-image. Results also support predictions of both direct and indirect effects of gender as well as direct effects of education and business degree. Results of a separate expert panel study are used to rank business accomplishments according to degree of entrepreneurship. Results of both studies reveal stark contrasts in the implied definition of entrepreneurship between entrepreneurship experts (academic and practitioner alike) and the general business community (as represented by the alumni). This raises questions about the meaning of the term “entrepreneurship”, what the word “entrepreneur”, in particular, conveys to the general public, and the implications for practice and future research.